Designing a Device to Assist the Deaf in Determining the Direction of Surrounding Sounds Using Arduino - Jafar, Umalbanin Ali Sahaib; Mohammed, Hiba Ayad Ahmed; Abd Hadi, Mustafa Qatiba Abd Ghaleb; Lazim, Moamel Firas Ghadban; Hadi, Hassan Sabah Mohammed (American Journal of Botany and Bioengineering, 2025)
Deaf and hard-of-hearing people face difficulties in identifying the sources of ambient sounds, which can expose them to daily risks and limit their integration into society. This research aims to develop a system based on artificial intelligence and sensors to analyze sound directions and inform the user via visual or vibrational signals. A prototype of the system was designed and field-tested, and the results achieved an accuracy of up to 85% in identifying sound directions in different environments. This project contributes to improving the quality of life for the deaf community by enhancing their environmental awareness and promoting their independence.